AB0962 Validity and Sensitivity To Change of The Semi-Quantitative Omeract Ultrasound Scoring System for Tenosynovitis in Patients with Rheumatoid Arthrit. (15th July 2016) - Ammitzbøll-Danielsen, M.; Østergaard, M.; Naredo, E.; Terslev, L.
Abstract : Background: Tenosynovitis is frequent in rheumatoid arthritis (RA) patients. In 2012 the Outcome Measures in Rheumatology (OMERACT) US group proposed a new tenosynovitis scoring system with a good inter-observer reliability. However, its interreader agreement longitudinally and the sensitivity to change during treatment have not been tested. Objectives: In a 6-months follow-up study of RA patients with US tenosynovitis, initiating treatment intensification with synthetic and/or biological disease-modifying anti-rheumatic drug (DMARD), to validate the semi-quantitative OMERACT US-scoring system of tenosynovitis by testing its interreader reliability, sensitivity to change, and comparison to clinical evaluation. Methods: US (by grey-scale (GS) and color Doppler (CD)) and clinical assessment of the flexor and extensor tendon sheaths of the clinically most affected hand and foot was performed at baseline and after 3 and 6 months. Tenosynovitis was assessed using the semi-quantitative scoring system (0–3) proposed by the OMERACT US group for GS and CD calculating a sum score (0–39 for the hand and 0–21 for the foot) for each patient. In 20 patients, US was done independently by 2 physicians at baseline and 6 months, to assess the inter-observer agreement. A GE Logiq E9 with a linear 6–15 ML probe was used. CD frequency was 7.5 MHz, a pulse repetition frequency =0.4 and gain just below the noise limit. The same Doppler settings were used for all examinations. A binary score for clinical tendon involvement (0–1) was also performed at the same locations as the US score, with reference to published recommendations (3), calculating a sum score (0–13 for the hand and 0–7 for the foot) Results: Fifty-one RA patients, planned for treatment intensification, were included: 43 women (age: mean 55.6; standard deviation (SD) 13.1) and 8 men (mean 49.1; SD 9.34). Thirty-four patients were anti-rheumatoid factor positive and 30 had early RA (duration <1 year). The interreader agreement, as assessed by the intra-class correlation coefficient (ICC) was very good at baseline and for change for GS sum scores (ICC Baseline=0.89; Change=0.89) and CD (ICC Baseline=0.95; Change=0.90) tenosynovitis. The smallest detectable change for change in scores was 0.97 for GS and 0.93 for CD. Tenosynovitis scores had decreased significantly at months 3 and 6 (Table 1 and figure 2 ). The sensitivity to change, as expressed by the standardized response mean from month 0–6, was high for GS and CD tenosynovitis (0.90 and 0.76, respectively), and moderate (0.59) for the clinical score (Table 1 ). Conclusions: The present study demonstrated an excellent interreader agreement for the OMERACT US scoring system for tenosynovitis and a high ability to detect changes over time. The high reproducibility and responsiveness of both GS and CD scores indicate that the OMERACT US scoring system is useful for diagnosing and monitoring of tenosynovitis in RA clinical trials and practice Disclosure of Interest: None declared